Qualidade de vida relacionada com os problemas bucais em mulheres antes e durante o tratamento quimioterápico do câncer de mama - Calmon, Marcela Vieira (2013)
To assess the prevalence of impacts produced by oral problems on quality of life and its possible association with sociodemographic variables, need for dental prosthesis, dental service utilization and clinical staging, and assess the impact of oral manifestations on quality of life in women before and during chemotherapy for breast cancer. Methodology: The survey was conducted in women with a histopathologic diagnosis of breast cancer at the Hospital Santa Rita de Cassia (HSRC), from January 2012 to January 2013. There were two studies: the first was observational cross and the second was longitudinal, the women were studied on three occasions. To order one, we selected all women with histological diagnosis of breast cancer treated at the HSRC between January and December 2012. To order two, the sample was calculated using the BioStat 5.0 and using the McNemar test. Data were organized using Microsoft Office Excel 2007 for Windows and analyzed using Statistical Package for Social Sciences (SPSS) version 20.0. For objective one, performed descriptive analysis of data by means of frequency tables with numbers and percentages for each of the items of the survey instrument. It was used qui-quadrado square or Fisher exact test. Was calculated odds ratio (OR) with a confidence interval of 95%, and used the method of Mantel-Haenzsel. For objective two, was performed descriptive analysis of data by means of frequency tables with numbers and percentages for each dimension OHIP in three stages of the research. It was applied the McNemar test, and the Kappa test. Adopted were significance levels below 5%. Results: Were studied 89 women who fulfilled the criteria for inclusion during the study period. The prevalence of impact of oral health on quality of life was 28.1% and was associated with lower income and utilization of dental services by urgency. For the second objective, were studied 41 women. There was an increase in the percentage impact of oral manifestations on quality of life of women surveyed from the first to the second stage of the research. The impact is significant on the dimensions functional limitation, physical pain and physical disability, interfering with essential conditions of women, such as speech and feeding. Conclusion: The antineoplastic therapy in women already have a high impact before the treatment and this condition is aggravated after chemotherapy. It is extremely important the integration of the dentist with the oncology team in patient care at all stages of the disease. These patients requiring oral care specific, need of monitoring before, during and after treatment cancer in an attempt to minimize the deleterious effects of chemotherapy, thus improving its quality of life.